Management of institutional digital library with Invenio software: IDS example, the Document Server IDEP - Antonin Benoît Diouf (My University, 2016)
The world is undergoing a digital revolution as during revolutions Earlier factors that have been profound changes in the evolution of man, Africa still remains outside the process and may be even more distanced from the most advanced continents in terms of development. This is why it is very commendable that wills manifest reflection to create frameworks, exchange and sharing of practices that are only beneficial for awareness on this important issue of time is the most widespread as possible in the continent. It is in this context the need to include the relevance of the creation of the International Conference on Libraries and archives Digital African (ICADLA), now in its third edition this year 2013 and other well initiatives that participate in the same movement. Taking advantage of the opportunity offered by this conference, it seemed important, even essential to share the experience of the African Institute of Economic Development and Planning (IDEP) United Nations in creating and managing a digital library. All the more that the Institute is at the crossroads roads after 50 years of accumulation and a documentary produced both internally and from external sources. It is then imperative to take part in the digital revolution course and make it available on the networks that we have as resources to discover. 6 months ago we set up a functional digital library with a minimal deployment costs, it related to the free and open nature of the software we used. Experience even more relevant to share the African context in general is marked by a scarcity of financial resources in the field of document management and librarianship. In this article we present our pan-African institution with filigree everything its specificity for documentation and which is the ingredient that is the basis of the draft creation of digital library. We then describe the functional characteristics of software before finishing with prospects on a continental scale, who register relationship with the need to make Africa a digital content provider like any other continents.